Pengaruh Penggunaan Smartphone Terhadap Perkembangan Bahasa Balita Di Wilayah Kerja Puskesmas Karang Tengah Kota Tangerang - Felda Elish; Ani Fadmawaty (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2025)
The phenomenon of smartphone use among children has drawn attention to toddler development. This stage, which spans from 12 to 59 months, is often referred to as the